Entering into dialogue with the taboo: Reflective writing in a social work human sexuality course - McEntarfer, Heather Killelea; Skiba, David; Robert, Sarah A. (Journal of Writing Research, 2012)
This paper examines a unique reflective writing assignment used in an undergraduate social work course on human sexuality. We ask what new understandings reflective writing mediates (Vygotsky, 1978) regarding sexual orientation, gender identity, and gender relationsĂ˘â‚¬â€ťoft-neglected topics within pre-professional academic programs. One goal for this assignment was to mediate future social workers' abilities to differentiate between thoughts and feelings, and we evaluate the degree to which students did so in their writing. By adapting Hatton and Smith's (1994) framework for analyzing reflective writing, we also distinguish between descriptive and dialogical reflection, identifying and analyzing examples of both within the students' writing. Findings suggest that students engaged primarily in descriptive reflection, but also engaged in some dialogical reflection. We argue that both are useful but that the latter mediates deeper and more useful learning. We present recommendations for enhancing reflective writing assignment design in pre-professional academic programs.